Sombong Dalam Alquran Dan Kontekstualisasi Ayat Sombong Studi Penafisiran Al-Maragi dalam Tafsir Al-Maragi - Taufikurrahman Taufikurrahman (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2018)
The Qur’an which literally means “perfect reading” is a chosen name of Allah that is truly appropriate, because there is not even one reading since mankind recognized the five thousand years of literacy that can rival the Al-Koran Al-Qur’an, perfect and noble reading. There is no reading like the Qur’an that is learned not only in terms of editorial composition and vocabulary choices, but also the contents expressed, implied even to the impressions that are generated. The Qur’an always gives new meaning to everyone who interprets it, without changing the meaning contained in it and without reducing the values that are to be conveyed to humans as a guide. Along with the dynamics of the times, the science of interpretation and the model of interpretation of the Qur’an also continues to grow and develop. The diversity of interpretations makes the treasure of knowledge excavated from the Qur’an very broad. Even this development will continue as long as Muslims continue to utilize all their potential and abilities to understand the Qur’an. This applies to every interpretation of the verses of the Qur’an which are to be interpreted. Included in this paper is the interpretation of arrogant verses in the Qur’an according to al-Maragi.